B Cell and CD4 T Cell Interactions Promote Development of Atherosclerosis - Tay, Christopher; Kanellakis, Peter; Hosseini, Hamid; Cao, Anh; Toh, Ban-Hock; Bobik, Alex; Kyaw, Tin (Frontiers in Immunology, 2020)
Reciprocal partnership between B and CD4 T cells is crucial for their optimum responses in adaptive immunity. Immune responses augmented by their partnership promote chronic inflammation. Here we report that interdependent collaboration between B and CD4 T cells augments their atherogenic function to promote lipid-induced atherosclerosis. Genetic deletion of the gene encoding immunoglobulin mu (μ) heavy chain (μMT) in ApoE-/- mice resulted in global loss of B cells including those in atherosclerotic plaques, undetectable immunoglobulins and impaired germinal center formation. Despite unaffected numbers in the circulation and peripheral lymph nodes, CD4 T cells were also reduced in spleens as were activated and memory CD4 T cells. In hyperlipidemic μMT-/- ApoE-/- mice, B cell deficiency decreased atherosclerotic lesions, accompanied by absence of immunoglobulins and reduced CD4 T cell accumulation in lesions. Adoptive transfer of B cells deficient in either MHCII or co-stimulatory molecule CD40, molecules required for B and CD4 T cell interaction, into B cell-deficient μMT-/- ApoE-/- mice failed to increase atherosclerosis. In contrast, wildtype B cells transferred into μMT-/- ApoE-/- mice increased atherosclerosis and increased CD4 T cells in lesions including activated and memory CD4 T cells. Transferred B cells also increased their expression of atherogenic cytokines IL-1b TGF-b, MCP-1, M-CSF and MIF, with partial restoration of germinal centers and plasma immunoglobulins. Our study demonstrates that interaction between B and CD4 T cells utilizing MHCII and CD40 is essential to augment their function to increase atherosclerosis in hyperlipidemic mice. These findings suggest that targeting B cell and CD4 T cell interaction may be a therapeutic strategy to limit atherosclerosis progression.